BMP-9 interferes with liver regeneration and promotes liver fibrosis. Issue 5 (23rd March 2017) - Breitkopf-Heinlein, Katja; Meyer, Christoph; König, Courtney; Gaitantzi, Haristi; Addante, Annalisa; Thomas, Maria; Wiercinska, Eliza; Cai, Chen; Li, Qi; Wan, Fengqi; Hellerbrand, Claus; Valous, Nektarios A; et al.
Abstract : Objective: Bone morphogenetic protein (BMP)-9, a member of the transforming growth factor-β family of cytokines, is constitutively produced in the liver. Systemic levels act on many organs and tissues including bone and endothelium, but little is known about its hepatic functions in health and disease. Design: Levels of BMP-9 and its receptors were analysed in primary liver cells. Direct effects of BMP-9 on hepatic stellate cells (HSCs) and hepatocytes were studied in vitro, and the role of BMP-9 was examined in acute and chronic liver injury models in mice. Results: Quiescent and activated HSCs were identified as major BMP-9 producing liver cell type. BMP-9 stimulation of cultured hepatocytes inhibited proliferation, epithelial to mesenchymal transition and preserved expression of important metabolic enzymes such as cytochrome P450. Acute liver injury caused by partial hepatectomy or single injections of carbon tetrachloride (CCl4 ) or lipopolysaccharide (LPS) into mice resulted in transient downregulation of hepatic BMP-9 mRNA expression. Correspondingly, LPS stimulation led to downregulation of BMP-9 expression in cultured HSCs. Application of BMP-9 after partial hepatectomy significantly enhanced liver damage and disturbed the proliferative response. Chronic liver damage in BMP-9-deficient mice or in mice adenovirally overexpressing the selective BMP-9 antagonist activin-like kinase 1-Fc resulted in reduced deposition of collagen and subsequent fibrosis. Conclusions: Constitutive expression of low levels of BMP-9 stabilises hepatocyte function in the healthy liver. Upon HSC activation, endogenous BMP-9 levels increase in vitro and in vivo and high levels of BMP-9 cause enhanced damage upon acute or chronic injury.